2020
DOI: 10.1186/s13058-020-01324-4
|View full text |Cite
|
Sign up to set email alerts
|

Targetable ERBB2 mutation status is an independent marker of adverse prognosis in estrogen receptor positive, ERBB2 non-amplified primary lobular breast carcinoma: a retrospective in silico analysis of public datasets

Abstract: Background: Invasive lobular carcinoma (ILC) accounts for 10-15% of primary breast cancers and is typically estrogen receptor alpha positive (ER+) and ERBB2 non-amplified. Somatic mutations in ERBB2/3 are emerging as a tractable mechanism underlying enhanced human epidermal growth factor 2 (HER2) activity. We tested the hypothesis that therapeutically targetable ERBB2/3 mutations in primary ILC of the breast associate with poor survival outcome in large public datasets. Methods: We performed in silico comparis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 38 publications
(66 reference statements)
3
12
0
2
Order By: Relevance
“…The acquisition of ERBB2 and ERBB3 mutations in ILC has been shown to be associated with an increased risk of relapse and poorer outcomes, likely representing an escape mechanism to endocrine therapy [ 44 ]. Indeed, a recent, large meta-analysis showed that ILCs account for 47% of all ERBB2 mutated (not amplified) cases, and that targetable ERBB2 mutations are an independent prognostic marker of poorer 10-year overall survival [ 80 ]. This team then postulated that mutation of ERBB2/3 may initiate alternate downstream activity (as opposed to ERBB2/3 amplification) and derived a gene expression signature to measure this.…”
Section: What Is New In Invasive Lobular Carcinoma?mentioning
confidence: 99%
“…The acquisition of ERBB2 and ERBB3 mutations in ILC has been shown to be associated with an increased risk of relapse and poorer outcomes, likely representing an escape mechanism to endocrine therapy [ 44 ]. Indeed, a recent, large meta-analysis showed that ILCs account for 47% of all ERBB2 mutated (not amplified) cases, and that targetable ERBB2 mutations are an independent prognostic marker of poorer 10-year overall survival [ 80 ]. This team then postulated that mutation of ERBB2/3 may initiate alternate downstream activity (as opposed to ERBB2/3 amplification) and derived a gene expression signature to measure this.…”
Section: What Is New In Invasive Lobular Carcinoma?mentioning
confidence: 99%
“…Additionally, Ecadherin loss appears to result in activation of the phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)/Akt signaling pathway, irrespective of oncogenic mutations in PIK3CA [12]. Somatic mutations in ILC differ from those in IDC, with increased prevalence of mutations in FOXA1, AKT1, PTEN, HER2, HER3, and FGFR4 seen in HR-positive, HER2negative ILC compared to HR-positive, HER2-negative IDC [8,13,14]. Within ILC, specific gene expression signatures have recently been described, providing evidence for heterogeneity within this tumor type and potential predictors of response to therapy [7,15,16] Upon clinical presentation, patients with ILC face unique challenges starting with delays in diagnosis and imprecision of clinical staging.…”
Section: Invasive Lobular Carcinoma Is a Distinct Biologic And Clinicmentioning
confidence: 99%
“…Recent studies have shown enrichment of activating HER2 mutations in ILC compared to IDC, with 5.7% of early stage ILC cases having such mutations compared to 1.4% of IDC cases [13]. Rates of HER2 mutations appear to be even more prevalent in certain subtypes of ILC, with up to 26% of pleomorphic ILC tumors harboring such mutations [51].…”
Section: Neratinib Her Mutation Basket Study (Summit)mentioning
confidence: 99%
“…Lower incidences of central nervous system metastases may indicate this inhibitor should be used for patients at high risk of this metastatic pattern [66]. There is some evidence this inhibitor may be used to target mutations in the tyrosine kinase domain of the HER2 receptor, even in HER2-tumours [67].…”
Section: Next Generation Treatmentsmentioning
confidence: 99%